REVISITING TRADITIONAL LINGUISTIC SCHOOLS - Titis Bayu Widagdo; Nasywa Fitri Azzahra; Renda Yuriananta (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to reexamine the historical and intellectual development of the traditional linguistic school and its contribution to the emergence of modern linguistics. Employing a systematic literature review method, data were collected from classical linguistic monographs, peer-reviewed journal articles, and published academic lecture notes. The analysis was conducted through a descriptive-chronological approach by comparing the ideas of major figures from the Greek and Roman periods, the Middle Ages, and the Renaissance, leading to the pre-structuralist era. In addition, this research investigates linguistic traditions in the Eastern world—particularly India and the Arab sphere—as a comparative perspective to Western scholarship. The findings indicate that traditional linguistics is predominantly prescriptive, centered on word-class classification, and foundational to subsequent linguistic theories.